Assessment of anaerobic bacterial diversity and its effects on anaerobic system stability and the occurrence of antibiotic resistance genes. (May 2016) - Aydin, Sevcan; Ince, Bahar; Ince, Orhan
Graphical abstract: Highlights: Most ARGs proliferated in sludge of the anaerobic treatment process. qPCR analysis is suitable approach of determination of ARGs. Anaerobic treatments contribute to emergence and spread of ARGs. Bacterial community was the main driver for the acquisition of ARGs. Abstract: This study evaluated the link between anaerobic bacterial diversity and, the biodegradation of antibiotic combinations and assessed how amending antibiotic combination and increasing concentration of antibiotics in a stepwise fashion influences the development of resistance genes in anaerobic reactors. The biodegradation, sorption and occurrence of the known antibiotic resistance genes (ARGs) of erythromycin and tetracycline were investigated using the processes of UV-HPLC and qPCR analysis respectively. Ion Torrent sequencing was used to detect microbial community changes in response to the addition of antibiotics. The overall results indicated that changes in the structure of a microbial community lead to changes in biodegradation capacity, sorption of antibiotics combinations and occurrence of ARGs. The enhanced biodegradation efficiency appeared to generate variations in the structure of the bacterial community. The results suggested that controlling the ultimate Gram-negative bacterial community, especially Acinetobacter -related populations, may promote the successful biodegradation of antibiotic combinations and reduce the occurrence of ARGs.